Ways of expressing locativity in Kazakh and Kyrgyz languages - Karoly Ласло; Iskakova Айсулу (Turkic Studies Journal, 2025)
The article analyzes the functional-semantic field (FSF) of locativity in the Kazakh and Kyrgyz languages. Functional linguistics in Kazakh is a relatively new field of study, with research on functional grammar emerging only in the late 20th century. In the Kyrgyz language, however, there is a paucity of scholarly work on this topic. Previous studies on linguistic units conveying spatial meaning have been conducted in isolation, and this issue has not been systematically addressed in Turkology. The article is divided into theoretical and practical sections. The theoretical part outlines the key concepts of functional analysis, including the distinction between systemic-structural and functional linguistics, the concept of extra-linguistic categories as the foundation of functional methodology, and the definition and structure of the FSF, consisting of a core and a periphery. In the practical section, based on collected data the FSF of locativity in Kazakh and Kyrgyz is determined. The study reveals that the conceptual basis of the FSF of locativity in both languages is grounded in spatial meanings. The core of the locativity field is polycentric, with spatial meaning expressed through both morphological and lexical units. Morphological elements in the core include the noun case markers (dative, locative, ablative), auxiliary parts of speech, adverbs, interrogative and demonstrative pronouns, and verbs. Lexical indicators include geographical terms, toponyms, different types of objects and units of measurement related to space. In the periphery, the spatial meaning becomes less distinct, manifesting through phraseological units in Kazakh and Kyrgyz, as well as syntactic structures such as phrases and sentences. The FSF of locativity in both languages shares a common conceptual foundation, exhibiting similar structures and linguistic units for expressing locativity. However, the fields differ in terms of their inherent semes. The differences are particularly noticeable in traditional units of measurement and fixed expressions, thereby facilitating a more profound comprehension of their structural intricacies and distinctive characteristics.These differences reflect the diversity of spatial perception and locativity across different cultures. The study establishes new possibilities for the comparative analysis of the functional and semantic systems of Turkic languages, thereby enhancing our comprehension of their structure and distinctive characteristics.